The Role of Motivational Disposition in EFL University Students’ Willingness to Communicate in English in Hungarian Higher Education: A Pilot Questionnaire Study - Kaw, Mai Nelly (GILE Journal of Skills Development, 2026)
Globalization and the spread of English as a global lingua franca have shifted second language (L2) motivation research toward learners’ self-concept and identity (Dörnyei, 2009; Ushioda, 2011). The expansion of global connections has increased the need for English proficiency and for learners’ readiness to use the language in academic and professional settings (MacIntyre et al., 1998). Although motivation and willingness to communicate (WTC) have received considerable attention, little research has examined their relationship among Hungarian university students both inside and outside the classroom. To address this gap, a questionnaire was developed and piloted with 100 participants. The instrument is a composite of adapted and original items, as well as newly developed items derived from interview findings that preceded this questionnaire study. This paper outlines the instrument development process and aims to validate a questionnaire that measures EFL university students’ motivational profiles and willingness to communicate in the Hungarian context, as well as to explore the relationship between these constructs. The results show that students’ motivation is primarily associated with their Ideal L2 Self, attitudes towards the learning community, and travel orientation. Correlation analyses reveal a strong relationship between intrinsic motivation and motivated learning behaviour. Regression analyses identify Ideal L2 Self as a significant predictor of willingness to communicate, with a stronger effect outside the classroom. In the Hungarian EFL context, students reported high levels of confidence and motivation in both classroom and out-of-classroom settings; nevertheless, their WTC was even stronger outside the classroom. This pattern indicates that their engagement with English extends beyond formal instructional requirements. These findings are preliminary; however, the questionnaire shows potential for reliable measurement, while further research with larger samples remains necessary.